In vivo transplantation of mammalian vascular organoids onto the chick chorioallantoic membrane reveals the formation of a hierarchical vascular network - Kowalski, William J.; Vatti, Shravani; Sakamoto, Tyler; Li, Wenling; Odutola, Sarah Rose; Liu, Chengyu; Chen, Guibin; Boehm, Manfred; Mukouyama, Yoh-suke (Scientific reports, 2025)
The dynamic remodeling of the nascent vascular network into a mature hierarchy is essential for embryo survival. Cell behaviors and signaling mechanisms are often investigated with animal models and perfused microchannels, giving insights into this process. To support these studies and enrich our understanding, we demonstrate a complementary approach using vascular organoids. Organoids initially form a primitive endothelial plexus lined with NG2 + /PDGFRβ + mural cell progenitors containing immature pericytes, but there is no formation of large-diameter vessels covered with αSMA + cells containing immature vascular smooth muscle cells (vSMCs). After transplantation to the chick chorioallantoic membrane, the network reorganizes into a branched architecture with large-diameter vessels covered by αSMA + cells. We additionally show that blood flow from the host circulation perfuses the organoid. Compared with the developing skin vasculature in mouse embryos, organoids successfully recapitulate vascular morphogenesis, both in vitro and after transplantation. The model described here presents a further approach to enhance the study of vascular remodeling.